2009
DOI: 10.1243/09544054jem1374
|View full text |Cite
|
Sign up to set email alerts
|

Changing from conveyor to work-cell-based systems to deal with fluctuations in demand

Abstract: As consumption patterns become increasingly sophisticated and manufacturers strive to improve their competitiveness, not only by offering higher quality at competitive costs, but also by providing a broader mix of products and keeping the range attractive by launching successive new products, turbulence in the markets has intensified. This has driven leading manufacturers to research the development of alternative production systems that are supposed to enable them to operate more responsively. This paper disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Manufacturers are looking for a cell-based approach to offer products with different varieties. As the cellbased approach involves more complex production flows so for this, conveyor line production systems are not suitable [5]. In cell-based manufacturing, the best way to handle the goods shifting between cells is the use of mobile-robots.…”
Section: Introductionmentioning
confidence: 99%
“…Manufacturers are looking for a cell-based approach to offer products with different varieties. As the cellbased approach involves more complex production flows so for this, conveyor line production systems are not suitable [5]. In cell-based manufacturing, the best way to handle the goods shifting between cells is the use of mobile-robots.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely recognized in the literature that 20 per cent to 50 per cent of manufacturing expenses are attributed to facility layout and material handling, and it has been reported that effective layout design may reduce these costs by at least 10-30 per cent [4,5]. Therefore, the right physical allocation of machines and equipment and the right selection and design of the materials handling system may contribute significantly to reducing the unit cost of the product, and may enhance the company's competitive position [6,7].…”
Section: Introductionmentioning
confidence: 99%